Binding of EphrinA5 to RET receptor tyrosine kinase: An in vitro study. - Yixin Liu; Heidi Kaljunen; Ana Pavić; Tuulia Saarenpää; Juha P Himanen; Dimitar B Nikolov; Adrian Goldman (PLoS ONE, 2018)
Eph/Ephrin signaling pathways are crucial in regulating a large variety of physiological processes during development, such as cell morphology, proliferation, migration and axonal guidance. EphrinA (efn-A) ligands, in particular, can be activated by EphA receptors at cell-cell interfaces and have been proposed to cause reverse signaling via RET receptor tyrosine kinase. Such association has been reported to mediate spinal motor axon navigation, but conservation of the interactive signaling pathway and the molecular mechanism of the interaction are unclear. Here, we found Danio rerio efn-A5b bound to Mus musculus EphA4 with high affinity, revealing structurally and functionally conserved EphA/efn-A signaling. Interestingly, we observed no interaction between efn-A5b and RET from zebrafish, unlike earlier cell-based assays. Their lack of association indicates how complex efn-A signaling is and suggests that there may be other molecules involved in efn-A5-induced RET signaling.